The Influence of Leadership Style and Organizational Culture on Employee Performance through Organizational Commitment as Intervening Variable - Torang Purba; Sumardi Lasise; Jumidah Maming (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
This study aims to examine and analyze the influence of leadership and organizational culture on employee performance through organizational commitment as an intervening variable of the Makassar New Port Project of PT. PP (Persero) Tbk. Data was collected by a survey method, using direct observation and questionnaire instrument made on the paper and distributed to 103 employees with three job divisions, namely finance & administration, engineering, and operational. Of the 103 employees, 103 responded. Data is then analyzed using the IBM SPSS Statistics 25 program. The results showed that leadership styles and organizational culture have a positive and significant direct effect on organizational commitment, leadership styles and organizational culture have a positive and significant direct effect on employee performance, Organizational commitment has a positive and significant direct effect on employee performance. The results of the analysis also show that leadership styles and organizational culture have no significant effect on employee performance through organizational commitment. This implies that leadership style, organizational culture, and organizational commitment play a key role in increasing employee performance.